1977
DOI: 10.1007/bf03041425
|View full text |Cite
|
Sign up to set email alerts
|

On the mode of action of triadimefon

Abstract: Besides its known systemic activity, triadimefon acts in the vapour phase.This vapour phase activity of triadimefon was shown for powdery mildew on cucumbers and barley in greenhouse experiments at concentrations recommended for use in the field (I00 and 250 pg/ml) and also at substantially lower concentrations.The degree of vapour phase activity is dependent on the distance from the spray deposit.In experiments with radiolabelled triadimefon, it was observed that gaseous material was deposited on untreated ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1978
1978
1997
1997

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…In plant disease control, a few com pounds have been reported to show fungici dal activity after redistribution in the va pour phase [1,3,4,6,7,[12][13][14]17]. In most cases the test organisms were different species of powdery mildew.…”
mentioning
confidence: 99%
“…In plant disease control, a few com pounds have been reported to show fungici dal activity after redistribution in the va pour phase [1,3,4,6,7,[12][13][14]17]. In most cases the test organisms were different species of powdery mildew.…”
mentioning
confidence: 99%
“…Significant or complete control of mildew on seedling barley has been obtained for 10 days by spraying leaves or feeding roots with 1-5 ppm triadimefon 1 or 2 days before inoculation (Buchenauer, 1976). Scheinpflug & Paul (1977) reported that triadimefon also has unusually powerful activity in the vapour phase at concentrations above 10 /ig/ml; plants distant from those sprayed with 277 /ig received 0-1 jug/g fresh weight of plant by contact with the vapour and were protected from mildew. This high vapour activity of triadimefon seems anomalous in view of its low vapour pressure (1 X 10~* mbar at 20°C).…”
Section: Measurement Of Fungicide Reaching Soil From Foliar Spraysmentioning
confidence: 99%
“…It has been claimed to move systematically after application to roots or leaves of cereals (Kasper et al, 1975) and basipetally in cucumber and barley (Scheinpflug and Paul, 1977). Its activity is probably enhanced as a result of considerable redistribution in the vapor phase.…”
Section: Introductionmentioning
confidence: 98%